2007
DOI: 10.1021/ac070651e
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Impedimetric Detection of Glycan−Lectin Interactions

Abstract: A compact biosensor for a label-free, rapid (<80 s) detection of glycan-lectin interactions using ac impedance measurements was developed for the first time. A galactose-binding peanut agglutinin (PNA) and sialic acid-binding Sambucus nigra agglutinin (SNA) were covalently surface-immobilized on the layered Cu/Ni/Au printed circuit board (PCB) electrodes. Samples of artificial and natural glycoconjugates consisting of (1) gold glyconanoparticles encapsulated with approximately 90-100 copies of TF-antigen disac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(102 citation statements)
references
References 35 publications
3
99
0
Order By: Relevance
“…Human Embryonic Stem Cell Culture-The National Institutes of Health-approved hESC lines, H1 and HSF-6, were maintained under feeder-free conditions using a chemically defined medium, X-VIVO 10 (Cambrex, Walkersville, MD), supplemented with human recombinant growth factors fibroblast growth factor and transforming growth factor-␤1 (80 and 0.5 ng/ml, respectively; R & D Systems (10). The cells are propagated on hESC-qualified Matrigel-coated plates (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Human Embryonic Stem Cell Culture-The National Institutes of Health-approved hESC lines, H1 and HSF-6, were maintained under feeder-free conditions using a chemically defined medium, X-VIVO 10 (Cambrex, Walkersville, MD), supplemented with human recombinant growth factors fibroblast growth factor and transforming growth factor-␤1 (80 and 0.5 ng/ml, respectively; R & D Systems (10). The cells are propagated on hESC-qualified Matrigel-coated plates (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…[25][26][27]30 In contrast, a linear increase from baseline impedance was observed when the SNA lectin biosensor was incubated with an increasing concentration of fetuin expressing a correct glycan epitope. [25][26][27]30 Apart from showing very high binding specicity towards the glycan epitope, these SNA lectin biosensors have demonstrated sensitivity for glycoprotein detection (e.g. fetuin) up to attomolar concentration.…”
Section: Glycoprotein Capture and Detectionmentioning
confidence: 94%
“…29 In fact, glycan structure specic interactions of a glycoprotein with lectins are very well demonstrated in the recent past mainly using sialic acid binding lectin biosensors. [25][26][27]30 Incubation of the SNA lectin biosensor with asialofetuin, a non-sialic acid expressing glycoform variant of glycoprotein fetuin, showed very minimal change in the baseline impedance. [25][26][27]30 In contrast, a linear increase from baseline impedance was observed when the SNA lectin biosensor was incubated with an increasing concentration of fetuin expressing a correct glycan epitope.…”
Section: Glycoprotein Capture and Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, electrode geometry has proven important with interdigitated electrode arrays providing improved sensitivity [39,48]. Impedance-based sensors have been used to monitor protein-carbohydrate [49] and proteinprotein [50,51] interactions. For example, Yu et al [52] reported multiplexed protein monitoring with an array of gold electrodes.…”
Section: Amperometric Sensorsmentioning
confidence: 99%